1976
DOI: 10.1021/jf60207a031
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and metabolic fate of hesperetin-3-14C

Abstract: D-proline (0.20 g), the preferential crystallization of D isomer was carried out in the same manner as described above. By repeating these procedures, L and D isomers were successively obtained. Table V shows the results obtained by the successive resolution of N-n-butyryl-DL-proline.Optical Resolution of Other IV-Acyl-DL-proIines.jV-Acetyl-DL-proline, iV-chloroacetyl-DL-proline, and Nisobutyryl-DL-proline could also be resolved in the same manner as described above. Although AMsobutyryl-DL-proline could not b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

1982
1982
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 7 publications
(9 reference statements)
1
24
1
Order By: Relevance
“…well documented that naringenin effectively quenches free radicals because of their 4 -hydroxyl group in the ␤-ring possessing electron donating properties and being on radical target which thereby prevent the membrane from free radical attack and thus protect the membrane and inhibit the lipid peroxidation (Amic et al, 2003). The lipophilic nature of naringenin can facilitate its adherence to lipid bilayer which might reduces the formation of free radicals and protects the cell membrane (Honohan et al, 1976). GSH and other thiol-containing proteins play a very crucial key role in cellular defense against Cd toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…well documented that naringenin effectively quenches free radicals because of their 4 -hydroxyl group in the ␤-ring possessing electron donating properties and being on radical target which thereby prevent the membrane from free radical attack and thus protect the membrane and inhibit the lipid peroxidation (Amic et al, 2003). The lipophilic nature of naringenin can facilitate its adherence to lipid bilayer which might reduces the formation of free radicals and protects the cell membrane (Honohan et al, 1976). GSH and other thiol-containing proteins play a very crucial key role in cellular defense against Cd toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…14 C] given either orally or intraperitoneally to rats, was recovered as 14 CO 2 , a by-product of hepatic metabolism (47). This suggests that at least 40% of the hesperetin dose reached the liver.…”
Section: Pharmacokineticsmentioning
confidence: 95%
“…14 C]-hesperetin in rats indicate that intestinal absorption of aglycone flavanones may be greater than 90% (47).…”
Section: Pharmacokineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…This acid is known to be a colonic metabolite of hesperetin [11,35]; in earlier studies, the formation of 4b from hesperetin and eriodictyol, respectively, was reported after oral ingestion by rats [36]. In addition, Honohan et al [37] also observed the formation of 4b after incubation of 4 with rat caecal flora.…”
Section: Hesperetinmentioning
confidence: 97%